1979
DOI: 10.1136/bjo.63.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Keratoplasty sensitivity.

Abstract: SUMMARY Analysis of graft sensitivity showed a return to normal after 3 years in only one-third of the eyes. It is not known whether this is due to regeneration of abnormal or superficial nerve fibres. Contact lens wearers showed less sensitivity than spectacle wearers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…By using a Cochet-Bonnet esthesiometer, Mathers et al 16 observed that corneas remained anesthetic until 18 months after penetrating keratoplasty. Ruben and 13,[16][17][18] and our results might be because other researchers used the Cochet-Bonnet esthesiometer, which is thought to stimulate different types of nerve endings. Myelinated Ad fibers are large-diameter, straight nerve fibers that run parallel to the corneal surface within the epithelial subbasal plexus.…”
Section: Discussionmentioning
confidence: 53%
“…By using a Cochet-Bonnet esthesiometer, Mathers et al 16 observed that corneas remained anesthetic until 18 months after penetrating keratoplasty. Ruben and 13,[16][17][18] and our results might be because other researchers used the Cochet-Bonnet esthesiometer, which is thought to stimulate different types of nerve endings. Myelinated Ad fibers are large-diameter, straight nerve fibers that run parallel to the corneal surface within the epithelial subbasal plexus.…”
Section: Discussionmentioning
confidence: 53%
“…Corneal hypoesthesia after penetrating keratoplasty is well known but highly variable with abnormal sensation observed up to 32 years after corneal surgery. [20][21][22][23][24] Niederer et al 18 noted significant reductions in subbasal nerve fiber density and nerve branching after keratoplasty. These alterations to the subbasal plexus are still apparent up to 40 years after penetrating keratoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Skriver [6] wrote about a regular corneal sensitivity in the center of the cornea after PK 12 months later. Ruben and Colebrook [18] showed that corneal sensitivity returns regularly after 3 years in one third of patients with keratoconus. Rao et al [7] stated that corneal sensitivity of the central area never returns on a regular basis.…”
Section: Discussionmentioning
confidence: 99%